How indirect tax contribute to gross national product (GNP) - Mohd Abdul Kadir, Juliana; Mohamed, Zulkifli; Idris, Mustaffa (Institut Pengurusan Penyelidikan, Pembangunan & Pengkomersilan, 2013)
The purpose of this study is to investigate different types of Indirect Taxes that effect to GNP by using Multiple Regression. Besides that, this research also would like to study which one of the variable that will become the leader and the follower between each other. This research will answer the question with applying Granger Causality Test. The data that have been used are GNP and Indirect Taxes in the case of Malaysia in 2000-2008 quarterly. GNP is dependent variable to the indirect taxes. We have found that different taxes respond differently to the GNP with the largest responses by import duties and excise duties.